2019
DOI: 10.1002/joc.6413
|View full text |Cite
|
Sign up to set email alerts
|

Dryness/wetness pattern over the Three‐River Headwater Region: Variation characteristic, causes, and drought risks

Abstract: The dryness/wetness patterns are a significant reference for stakeholders in developing reasonable strategies in regard to water resource management, prediction, prevention of extreme events, and management of agricultural activities; however, no attempts have been made to systematically quantify the dryness/wetness patterns and drought conditions over the Three‐River Headwater Region (TRHR) of China, where the ecosystem is highly sensitive to climate change. The spatio‐temporal characteristics of dryness/wetn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…The ecosystem in the TRHR is mainly composed of alpine grassland, wetland, glacier and alpine permanent snow cover. It is an important ecological barrier and an ecological regulation area with the largest influences range in the middle and lower reaches of rivers and their surrounding areas, and the variation of precipitation has a bearing on the water ecological security of China and even Asia (Li et al 2020).…”
Section: Study Areamentioning
confidence: 99%
“…The ecosystem in the TRHR is mainly composed of alpine grassland, wetland, glacier and alpine permanent snow cover. It is an important ecological barrier and an ecological regulation area with the largest influences range in the middle and lower reaches of rivers and their surrounding areas, and the variation of precipitation has a bearing on the water ecological security of China and even Asia (Li et al 2020).…”
Section: Study Areamentioning
confidence: 99%
“…However, these limitations were addressed by the development of the standardized precipitation evapotranspiration index (SPEI) [22]. The following literature extensively summarizes recent SPEI based studies at a regional scale, temporal scale, types of datasets used and statistical method used [23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Using different drought indices, most of these studies revealed that SPEI is most sensitive to drought conditions due to the evaporative demand component (as demonstrated in potential evapotranspiration (PET)) indicating SPEI importance as a favorable drought index.…”
Section: Introductionmentioning
confidence: 99%
“…According to the linear fitting results, the average increase rate of precipitation in 21 years is 45.22 mm/10 a, especially between 2016-2020, the precipitation increase trend is more evident. During the same time period, the increase in precipitation in the Three Rivers source was close to 50 mm/10 a, which was higher than the global average, areas at the same latitude, and the whole region of China [31,32]. To sum up, the study area presents a warm-humid climate trend.…”
Section: Discussionmentioning
confidence: 62%